Isobutylamides from piper ridleyi - Ahmad, Farediah; Jamil, Shajarahtunnur; Read, Roger W. (Elsevier Science Ltd, 1995)
Extraction of the stems and leaves of Piper ridleyi with ether afforded N-isobutyl-15-(3',4'-methylenedioxyphenyl)- 2E,4E,12E-pentadecatrienamide (ridleyamide), as well as the known amide, retrofractamide, and sterols.